COLLABORATIVE GOVERNANCE DALAM PENCEGAHAN PENYEBARAN TUBERKULOSIS PARU DI RUMAH SAKIT PARU PROVINSI JAWA BARAT - Tia Mustiasih (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Collaborative Governance is a form of governance structure in which one or more public agencies directly relate to non-state stakeholders in a formal, consensus-oriented, deliberative decision-making process, and leads to the formulation or implementation of public policies, or can also take the form of program management. or public assets. Collaborative Governance is the Government's effort in an effort to minimize the transmission of Tuberculosis in West Java. This study was conducted to analyze the collaborative process of preventing the transmission of Tuberculosis in West Java. In addition, this study aims to provide strategic recommendations for effective collaborative governance in the context of preventing tuberculosis transmission. This study uses a qualitative approach with descriptive methods, data collection techniques through interviews and literature studies. The results of this study indicate that the collaborative governance process for preventing TB transmission in West Java in general is not optimal, there are several things that need to be improved to encourage the collaborative governance process of actors, namely the need for involvement of the private sector and the community as well as increasing the intensity of meetings between actors and increasing the role of leadership in collaborative governance in preventing tuberculosis transmission in West Java. This research is expected to enrich academic studies on collaborative governance in the realm of public policy and can be used as a reference for those who wish to contribute to the prevention of tuberculosis transmission by collaborating.